Knowledge, Attitude and Practice of Healthcare Providers on Advocating Diabetic Patients’ Insulin Self-Titration - Ying Hu, Mery Wei; Hatah, Ernieda Md; Loganadan, Navin Kumar; Robert, Sarah Anne; Hamid, Zulfikri Abdul; Foong, Sook Yeng (International Journal of Human and Health Sciences (IJHHS), 2024)
Objectives: This study aimed to evaluate the knowledge, attitude, and practice of healthcare providers (HCPs) in promoting insulin self-titration among type 2 diabetes (T2DM) patients and identify factors influencing their practices. Method: A cross-sectional survey was undertaken from April to June 2023, focusing on doctors, pharmacists, and nurses overseeing patients with T2DM undergoing insulin treatment at three tertiary hospitals in Malaysia. The study included HCPs who counsels insulin use, excluding those who did not provide informed consent. The self-developed online survey, meticulously validated, encompassed sections delving into respondents' demographics, knowledge, attitudes, and practices concerning insulin self-titration. Survey dissemination employed messenger applications or email, and participants were given a two-week window to fulfill the survey, reminders sent when necessary. Participation in the study was entirely voluntary. Any incomplete form cannot be submitted. Results: A total of 107 participants responded to the survey, 102 were included in the final analysis. Majority of the respondent (n = 53, 52.0%) demonstrated good knowledge on insulin titration practice, with majority (n =99, 97.1%) recognizing the importance of self-monitoring in insulin self-titration. Correct knowledge on carbohydrate exchange and insulin carbohydrate ratio was reported by 70.6% and 66.7% of the respondents, respectively. The survey revealed significantly higher knowledge scores related to fixed prandial insulin titration than flexible prandial insulin titration. Positive attitudes were reported by 50.0% of respondents. Majority of respondents (n=89, 87.2%) agreed that insulin self-titration can help minimize hypoglycemia episodes. However, some expressed hesitation in encouraging it among elderly patients (n=25, 24.5%), those with lower education levels (n=25, 24.5%), and insulin-naive patients (n=20, 19.6%). Approximately 55.0% of respondents exhibited good practice. Predictors of good practice included knowledge score, attendance of diabetes management training, patient caseload, and profession type. Conclusion: HCPs' advocacy for insulin self-titration requires improvement to mitigate clinical inertia. Additional training, especially focusing on strategies to overcome hypoglycemia, utilization of patient-assistance tools, and technology adoption, is recommended for comprehensive professional development. These findings contribute to the ongoing discourse on refining diabetes management practices in clinical settings. International Journal of Human and Health Sciences Supplementary Issue 02: 2024 Page: S18-S19